Sean Foran: capstone - Foran, Sean, artist (Colorado State University. Libraries, 2018)
The artist's statement: "Think like a businessman, create like an artist." In most forms of art, the artist creates mostly for themselves and mostly for the individual with pulls of emotion. In graphic design, no matter the platform, we are always creating work for a business or an entity of some kind. Our success in the world only comes with the success that we bring someone else's business. We have to compel their customers to invest purely through visual communication. We have to think like a marketer would, evaluating the audience in every aspect in conjunction with our clients company. What is the demographic of the audience? What are they interested in? What feeds their emotions? These are the questions a designer must ask themselves when delving into a project. We're here to market our clients ideals through pleasing aesthetics and to influence an audience's perception of music, of a book or an invent. The client creates the ideologies and we allow the world view them through our creations.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design